Answer:
In standard form it is x^4 - 12x^3y + 54x^2y^2 - 108x y^3 + 81y^4.
Step-by-step explanation:
(3y)^4 + 4C1(3y)^3(-x) + 4C2(3y)^2(-x)^2 + 4C3(3y)(-x)^3 + (-x)^4
= 81y^4 - 108y^3x + 54y^2x^2 - 12yx^3 + x^4
1. n=7
2. w= 7.75
3. f= -15
4. y = 66
5. g=42
6. p= 2
Answer:
26
hope this heps and pls mark brainliest :))
Step-by-step explanation:
Answer:
Table 1(red)
Step-by-step explanation:
A proportional relationship will have a constant of proportionality between y and x all through the data given.
Constant of proportionality, k = y/x
Table 1 (red):
y/x = 5/1 = 10/2 = 20/4 = 5
k = 5 all through, therefore, this table show a proportional relationship between x and y
Table 2 (blue):
y/x = 1/6 ≠2/9 ≠ 4/15
This doesn't have a constant of proportionality, k, that is the same all through in the given table of values. Therefore, it doesn't show any proportional relationship between x and y